An extracytoplasmic protein and a moonlighting enzyme modulate synthesis of c‐di‐AMP in Listeria monocytogenes. (21st April 2020) - Gibhardt, Johannes; Heidemann, Jana L.; Bremenkamp, Rica; Rosenberg, Jonathan; Seifert, Roland; Kaever, Volkhard; Ficner, Ralf; Commichau, Fabian M.
Summary: The second messenger cyclic di‐AMP (c‐di‐AMP) is essential for growth of many bacteria because it controls osmolyte homeostasis. c‐di‐AMP can regulate the synthesis of potassium uptake systems in some bacteria and it also directly inhibits and activates potassium import and export systems, respectively. Therefore, c‐di‐AMP production and degradation have to be tightly regulated depending on the environmental osmolarity. The Gram‐positive pathogen Listeria monocytogenes relies on the membrane‐bound diadenylate cyclase CdaA for c‐di‐AMP production and degrades the nucleotide with two phosphodiesterases. While the enzymes producing and degrading the dinucleotide have been reasonably well examined, the regulation of c‐di‐AMP production is not well understood yet. Here we demonstrate that the extracytoplasmic regulator CdaR interacts with CdaA via its transmembrane helix to modulate c‐di‐AMP production. Moreover, we show that the phosphoglucosamine mutase GlmM forms a complex with CdaA and inhibits the diadenylate cyclase activity in vitro . We also found that GlmM inhibits c‐di‐AMP production in L. monocytogenes when the bacteria encounter osmotic stress. Thus, GlmM is the major factor controlling the activity of CdaA in vivo . GlmM can be assigned to the class of moonlighting proteins because it is active in metabolism and adjusts the cellular turgor depending on environmental osmolarity.